2007
DOI: 10.1182/blood-2006-03-007112
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral-mediated RNAi inhibition of Sbds in murine hematopoietic progenitors impairs their hematopoietic potential

Abstract: Shwachman-Diamond syndrome (SDS) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 39 publications
10
46
0
1
Order By: Relevance
“…Lentiviral vector-mediated RNA interference technology combines the advantages of a lentiviral vector with those of an RNA interference sequence that is specifically targeted to inhibit gene expression. These tools are effective in a variety of mammalian cells and numerous disease models (Nishitsuji et al, 2004;Gonzalez-Alegre, et al, 2005;Raoul et al, 2005;Rawls et al, 2007). Since Stewart et al (2003) first reported the use of this technology, it has been used widely to study disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviral vector-mediated RNA interference technology combines the advantages of a lentiviral vector with those of an RNA interference sequence that is specifically targeted to inhibit gene expression. These tools are effective in a variety of mammalian cells and numerous disease models (Nishitsuji et al, 2004;Gonzalez-Alegre, et al, 2005;Raoul et al, 2005;Rawls et al, 2007). Since Stewart et al (2003) first reported the use of this technology, it has been used widely to study disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These syndromes are heterogeneous in their clinical presentations: for example, patients with ShwachmanDiamond syndrome (SDS) with confirmed mutations in the SBDS gene (Chr7q11) may not have all the characteristic features of neutropenia, skeletal defects and pancreatic insufficiency [4]. There is emerging evidence that loss of Shwachman-Bodian-Diamond syndrome (SBDS) protein affects haematopoeisis and numbers of circulating B lymphocytes [5]. Craniofacial malformation syndromes such as Treacher-Collins syndrome, caused by haploinsufficiency of the treacle protein, also affect the cells of the immune system [6], and a broader immunological defect has been described in the congenital anaemia of Diamond-Blackfan syndrome (Diamond-Blackfan anaemia: DBA) [7].…”
Section: Introductionmentioning
confidence: 99%
“…[67][68][69] iPSCs derived from SDS patients manifest deficits in exocrine pancreatic and hematopoietic differentiation and enhanced apoptosis. 70 Deletion of murine Sbds resulted in early embryonic lethality.…”
Section: Shwachman-diamond Syndrome: Molecular Pathophysiologymentioning
confidence: 99%